2022
DOI: 10.4269/ajtmh.21-1058
|View full text |Cite
|
Sign up to set email alerts
|

Food Security, Conflict, and COVID-19: Perspective from Afghanistan

Abstract: Afghanistan, a country challenged by war and conflicts, has been in a state of turmoil for several years. The prolonged suffering has brought many challenges to the country’s inhabitants. Among these, food security is one important cause for concern. Food security occurs when people continuously have physical and economic access to adequate, safe, and nutritious food to meet their dietary requirements and food preferences for a functional and healthy life. Amid the pandemic, Afghanistan has witnessed a large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…COVID-19 pandemic caused a significant number of deaths worldwide, but the prevalence of comorbidities [7,8], lower education levels, socioeconomic inequalities as the healthcare system inexperience to deal with the pandemic [9,10] contributed to the increase of COVID-19 cases and deaths in low-and middle-income countries (LMICs) [11][12][13]. Most of these countries still show inadequate vaccination programs, lack of an accurate and rapid diagnosis as well as poor viral surveillance [10,[14][15][16], contributing for the emergence of COVID-19 waves and new SARS-CoV-2 variants [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 pandemic caused a significant number of deaths worldwide, but the prevalence of comorbidities [7,8], lower education levels, socioeconomic inequalities as the healthcare system inexperience to deal with the pandemic [9,10] contributed to the increase of COVID-19 cases and deaths in low-and middle-income countries (LMICs) [11][12][13]. Most of these countries still show inadequate vaccination programs, lack of an accurate and rapid diagnosis as well as poor viral surveillance [10,[14][15][16], contributing for the emergence of COVID-19 waves and new SARS-CoV-2 variants [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Afghanistan’s continuous struggle has created several difficulties for the country’s population. Afghanistan has seen a significant rise in food shortfalls because of its reliance on neighboring nations during the epidemic [ 17 ]. Individuals attain food security when they have continuous physical and economic access to an adequate supply of safe and nutritious food that meets their dietary demands and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Other health-related implications of food insecurity have been observed in many countries, including multiple sub-Saharan African countries, such as Mali, Niger, and Sudan, as well as Yemen. 30 , 31 These countries have an increased case-fatality ratio for COVID-19, rank high on at least three malnutrition indicators, and show a moderate positive association with iron deficiency, highlighting how long-term food insecurity is related to ill health. 30 Additionally, in one Yemeni study, measles incidence was reported to be three times higher among severe acute malnutrition children, and diarrhea, fever, and cough were also significantly higher.…”
Section: Implications Of Food Insecurity In Yemenmentioning
confidence: 99%